Herded subjects: forced transfers of the kulliñ in current texts of Argentine and Chilean Patagonia (Anclajes, 2020)
In this work I investigate representations of the forced displacements of native peoples of southern Argentina and Chile (1870-1900) as arreo, in a set of current texts of the southern cultural area; this texts belongs to Liliana Ancalao, Gustavo de Vera and Juan Riveros. The relations between subject, body and merchandise linked to livestock resignify the forced transit, from the extermination of the austral peoples during the processes of colonization of the 19th century, to the detentions in the framework of the last Chilean military civic dictatorship (1973-1990). The livestock metaphor elides and fissures, in a broad sense, the language of the State which intercepts and updates discussions about the national literatures considered to be national.
Keywords: Argentine literature; Chilean literature; native peoples; displacements; XXI century